Longitudinal Quality-of-Life Outcomes of Skull Base Chondrosarcoma Patients following Surgical Resection - Taniguchi, Seika; Kam, Jeremy; Kirszbaum, Castle-Mendel; Akagami, Ryojo (Journal of Neurological Surgery Part B: Skull Base, 2024)
Objective Owing to the rarity of skull base chondrosarcomas (CS), much of its natural history and long-term impact on patient quality of life (QoL) are not well studied. This novel study demonstrates QoL among CS patients following radical treatment constituting surgery and postoperative radiotherapy over 2 decades.Study Design Retrospective review and prospective data collection to obtain patient demographic, tumor characteristics, clinical symptoms, and patient-reported QoL outcomes using the 36-Item Short Form Health Survey (SF-36).Setting/Participants Patients diagnosed with CS who underwent radical intent surgical resection by the senior author and adjuvant early postoperative proton beam therapy.Results Twenty-eight skull base CS patients were identified, with 19 patients completing full treatment course. Mean long-term follow-up was 148.9 months. Diplopia symptom resolution was high. No significant deterioration in SF-36 Physical Health Component (PHC) and Mental Health Component (MHC) scores was observed at postoperative and long-term follow-up. General health was stable initially but deteriorated in long term (Δ −18.88, minimal clinically important difference [MCID]: 9.86, p = 0.04). Compared with age-matched Canadian control patients, CS patients reported similar PHC scores at baseline and follow-up. CS patients reported lower MHC scores (45.8 vs. 50.9, p = 0.13) preoperatively, which persisted at follow-up decreasing by 1.9 (43.9 vs. 53.7, p = 0.03); this difference, however, did not reach MCID threshold of Δ 5.9.Conclusion We present the longest follow-up data on CS demonstrating stable long-term QoL with aggressive surgery. Tumor control was high and preoperative tumor size did not affect long-term QoL. Preoperative QoL was lower among CS compared with Canadian normative data. Postoperatively, only the decline in physical functioning QoL scores exceeded MCID. At long-term follow-up, the decline in physical functioning, social functioning, and general health exceeded MCID. Overall, QoL among CS patients remained lower at long-term follow-up despite absence of tumor progression and resolution of symptoms.
Keywords: chondrosarcoma; quality of life; skull base tumor; SF-36; skull base oncology